Progesterone-dependent expression of keratinocyte growth factor mRNA in stromal cells of the primate endometrium: keratinocyte growth factor as a progestomedin (The Rockefeller University Press, 1994)
In vitro studies have shown that keratinocyte growth factor (KGF, also known as FGF-7) is secreted by fibroblasts and is mitogenic specifically for epithelial cells. Therefore, KGF may be an important paracrine mediator of epithelial cell proliferation in vivo. Because stromal cells are thought to influence glandular proliferation in the primate endometrium, we investigated the hormonal regulation and cellular localization of KGF mRNA expression in the rhesus monkey uterus. Tissues were obtained both from naturally cycling monkeys in the follicular and luteal phases of the cycle, and from spayed monkeys that were either untreated or treated with estradiol (E2) alone, E2 followed by progesterone (P), E2 plus P, or E2 plus P plus an antiprogestin (RU 486). Northern blot analysis of total RNA with 32P- labeled probes revealed that the level of KGF mRNA in the endometrium was 70-100-fold greater in the luteal phase or after P treatment than in untreated, E2-treated, or follicular phase animals. Northern analysis also showed that KGF mRNA was present in the myometrium but was unaffected by hormonal state. RU 486 treatment prevented the P- induced elevation of endometrial KGF mRNA. P-dependent elevation of endometrial KGF expression was confirmed by measurement of KGF protein in tissue extracts using a two-site enzyme-linked immunosorbent assay. In situ hybridization with nonradioactive digoxigenin-labeled cDNA probes revealed that the KGF mRNA signal, which was present only in stromal and smooth muscle cells, was substantially increased by P primarily in the stromal cells located in the basalis region. Smooth muscle cells in the myometrium and the walls of the spiral arteries also expressed KGF mRNA, but the degree of this expression did not differ with hormonal state. P treatment led to increased proliferation in the glandular epithelium of the basalis region and to extensive growth of the spiral arteries. We conclude that the P-dependent increase in endometrial KGF resulted from a dual action of P: (a) a P- dependent induction of KGF expression in stromal cells, especially those in the basalis (zones III and IV), and (b) a P-dependent increase in the number of KGF-positive vascular smooth muscle cells caused by the proliferation of the spiral arteries. KGF is one of the first examples in primates of a P-induced, stromally derived growth factor that might function as a progestomedin.